2015
DOI: 10.1186/1129-2377-16-1
|View full text |Cite
|
Sign up to set email alerts
|

Contact heat evoked potentials and habituation measured interictally in migraineurs

Abstract: BackgroundA lack of habituation of different evoked potential modalities in migraine patients in-between attacks has been suggested.MethodsThis study investigates cortical response after painful stimuli evaluated by contact heat evoked potentials (CHEPs) and quantitative sensory testing (QST) during the migraine-free interval. We enrolled 22 migraine patients and 22 healthy subjects.ResultsCortical potentials after contact heat stimulation of the cheeks and the volar forearm at a temperature of 51°C showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 37 publications
7
94
0
Order By: Relevance
“…The PHQ‐9 is a multipurpose instrument for screening, diagnosing, monitoring, and measuring the severity of depressive symptoms, with possible scores ranging from 0 to 27. The PHQ‐9 Korean version has been validated previously with several populations, including older adults (Han, Jo, Kwak, Pae, Steffens, Jo, & Park, 2008), clinical patients (Seo and Park, 2015), students (Yoon, Lee, Pae, Yoon, Patkar, Steffens, & Kim, 2014) and Korean‐Americans (Shin, Park, Cho, Chiu, Bang, H., & Bernstein, 2010); a score of 10 or higher has been validated in clinical studies as defining depression (Kroenke et al, 2001). Since this scale was included only in the 2014 wave, we could not include prior KNHANES data sets in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The PHQ‐9 is a multipurpose instrument for screening, diagnosing, monitoring, and measuring the severity of depressive symptoms, with possible scores ranging from 0 to 27. The PHQ‐9 Korean version has been validated previously with several populations, including older adults (Han, Jo, Kwak, Pae, Steffens, Jo, & Park, 2008), clinical patients (Seo and Park, 2015), students (Yoon, Lee, Pae, Yoon, Patkar, Steffens, & Kim, 2014) and Korean‐Americans (Shin, Park, Cho, Chiu, Bang, H., & Bernstein, 2010); a score of 10 or higher has been validated in clinical studies as defining depression (Kroenke et al, 2001). Since this scale was included only in the 2014 wave, we could not include prior KNHANES data sets in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An inability to habituate to pain or a fast disruption of habituation (dishabituation) may foster chronic pain problems [3]. Several studies have found that certain pain types, such as fibromyalgia [47,56,57], migraine [2,16,51,58,59] and chronic low back pain [15,37,43,61], are characterized by deficits in habituation to pain. Future research needs to unravel whether the attenuation of habituation in chronic pain patients stems from deficits in sensory processing and/or from deficits in contextual processing, for instance by activation of responses to pain in inappropriate contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these setbacks, research related to TRPV1 antagonism shows promising results. For example, one researcher evaluated the mechanism and efficacy of two TRPV1 antagonists, JNJ-38893777 and JNJ017203212, in the treatment of migraine headaches [29]. Their work demonstrated a significant reduction in calcitonin-related gene peptide (CGRP) release from the trigeminal system following administration [29].…”
Section: Transient Receptor Potential Cation Channel (Trp) Pharmacmentioning
confidence: 99%
“…For example, one researcher evaluated the mechanism and efficacy of two TRPV1 antagonists, JNJ-38893777 and JNJ017203212, in the treatment of migraine headaches [29]. Their work demonstrated a significant reduction in calcitonin-related gene peptide (CGRP) release from the trigeminal system following administration [29]. Notably, these antagonists decreased CGRP more significantly than sumatriptan, a widely used migraine treatment [29].…”
Section: Transient Receptor Potential Cation Channel (Trp) Pharmacmentioning
confidence: 99%
See 1 more Smart Citation